Eco-innovation, sustainable supply chains and environmental performance in European industries - Valeria Costantini; Francesco Crespi; Giovanni Marin; Elena Paglialunga (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
The introduction and adoption of green technologies are considered the most cost effective way to reduce environmental pressure without compromising economic competitiveness. The scientific literature has emphasized the crucial role played by diffusion pathways of green technologies along the supply value chain, but empirical quantitative findings on the effectiveness of green technologies in improving environmental performance are scarce. The objective of this paper is to highlight the role of inter-sectoral linkages in shaping the influence played by eco-innovations on sectoral environmental performance. Empirical findings show that both the direct and indirect effects of eco-innovations help reduce environmental stress and that the strength of these impacts varies across the value chain depending on the technology adopted and the type of pollutant under scrutiny. The main implications we can deduce are that, first both corporate and policy governance strategies should specifically address the goal of maximizing environmental gains that can be achieved through the development and adoption of clean technologies along the supply chain, and second both strategies should be coordinated in order to minimize the costs for reducing environmental pressures.
Keywords: 330; eco-innovation; environmental performance; inter-sectoral linkages; international spillovers; value chain; sustainable production; governance systems